Visita de animal de estimação: proposta de atividade terapêutica assistida por animais a pacientes internados em hospital oncológico - Rocha, Regina Célia (2015)
The pets visit has been coming in this institution since 2011 and professionals in Health Psychology Team with specialization in ATAA coordinate it. The animal is part into the psychological treatment of patients, such as care and comfort references, basic conditions to cope with cancer. The animal may be a reference to improve the quality of life during treatment and hospitalization, reflecting the strong bond that exists in the relationship, in care measures. Have the opportunity to see the pet, even if for the last time brings a sense, providing opportunities on reframing illness and life - through mendering and renewing therapeutic effects. This study aimed to observe the effects of ATAA, here characterized as 'Pets for Business Programme', in a group of three patients with oncological diseases, admitted to ICESP - Institute of São Paulo State Cancer - Frias Octavius Oliveira, comparing them to the literature on the ATAA. According to literature (Brickell, 1984; Struckus, 1989; Wall, 1994; McVarisch, 1995; Panzer-Koplow, 2000; Sorrell, 2006; Souter & Miller, 2007), the effectiveness of Animals Visit Program ICESP improves and balances the psychological state of cancer patients and their families, enhancing their coping resources on life quality improvement both patients and their families, increasing resilience which minimizes psychologic and behavioral symptoms that interfere into treatment and hospitalization, reducing stress, pain and isolation inherent in the process (DIEFENBECK, BOUFFAR, MATUKAITIS, HASTINGS, and COBLE, 2010; HOROWITZ, 2010). Thus, the Animals Visit Program to ICESP confirms the theory there is a great need to re-humanize health practices, developing and providing up humanistic resources for care. It is not just an ethical issue but also rather an urgent need in healthcare paradigm